The value of "z" equals 8
Answer:
5.3
Step-by-step explanation:
Use Pyth Theorem
a^2 + b^2 = c^2
6^2 + b^2 = 8^2
36 + b^2 = 64
b^2 = 28
Sq root of 28 = 5.3
The square root of 51.84 is 7.2
25.13cm^2 or 8pi. The radius of a circle is 2 x pi x r^2. R is the radius. 2 x pi x 2^2cm -> 2 x pi x 4cm -> 8cm x pi -> 25.13cm^2. Leaving the answer in terms of pi would be 8pi.
Pick 2 pairs of equations t<span>hen use addition and subtraction to eliminate </span>the same variable<span> from both pairs of equations then it is left with 2 variables
</span>Pick two pairs
<span><span>4x - 3y + z = - 10</span><span>2x + y + 3z = 0
</span></span>eliminate the same variable from each system
<span><span>4x - 3y + z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>4x - 3y + z = - 10</span>
<span>-4x - 2y - 6z = 0</span>
<span>-5y - 5z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>- x + 2y - 5z = 17</span>
<span>2x + y + 3z = 0</span>
<span>-2x + 4y - 10z = 34</span>
<span>5y - 7z = 34
</span></span>Solve the system of the two new equations:
<span><span>-5y - 5z = - 10</span>
<span>5y - 7z = 34</span>
<span>-12z = 24</span>
which is , <span>z = - 2</span>
<span>-5y - 5(- 2) = - 10</span>
<span>-5y = - 20</span>
wich is , <span>y = 4
</span></span>substitute into one of the original equations
<span>- x + 2y - 5z = 17</span>
<span>- x + 2(4) - 5(- 2) = 17</span>
<span>- x + 18 = 17</span>
<span>- x = - 1</span>
<span>x = 1</span>
<span>which is , </span><span>(x, y, z) = (1, 4, - 2)</span><span>
</span>Does 2(1) + 4 + 3(- 2) = 0<span> ? Yes</span><span>
</span>